Stability of Lyophilized Homemade Control Serum After Reconstitution on SGOT and SGPT Levels Stored in Freezer at Temperature (-2° to -4°C) and -20°C for 8 Weeks - Kadek Profit Hartani; Anik Handayati (Universitas Nahdlatul Ulama Surabaya, 2023)
Improving health laboratory services is closely related to strengthening the quality of health laboratories. Serum control is part of the quality assurance of health laboratories. Lyophilized homemade serum is a type of homemade control serum. This research aims to determine the stability of lyophilized homemade control serum against Serum Glutamic Oxaloacetic Transaminase (SGOT) and Serum Glutamic Pyruvic Transaminase (SGPT) levels. This research used an experimental method with pooled sera as research material stored at -2°C to -4°C and -20°C for 8 weeks. Pooled sera were obtained from respondents who had no history of disease, were free from HIV, AIDS, and HBsAg. The research was conducted at the Reference Laboratory and Clinical Chemistry Laboratory Politeknik Kesehatan (Poltekkes) Kementerian Kesehatan, Surabaya. The results of the study were data analysis using linear regression test. The SGOT parameter at freezer temperature (-2 to -4°C) showed that the storage time had an effect of 90.97% with an error component of 9.03%. At freezer temperature (-20°C), the result of storage time has an effect of 78.71% with an error component of 21.29%. In the SGPT parameter with freezer temperature (-2 to -4°C), the result of storage time has an effect of 96.71% with an error component of 3.29%. At freezer temperature (-20°C), the result of storage time has an effect of 91.47% with an error component of 8.53%. The results of the SGOT and SGPT examinations did not exceed the limits of ±2SD and ±3SD The CV on the SGOT and SGPT examinations also did not exceed the CCV limits, which is to be stable.